Pentingnya Internal Marketing dalam Keberhasilan Koperasi - Nurwati, Ucu (Universitas Koperasi Indonesia, 2024)
Cooperatives can improve the welfare of their members if they can increase added value for members. Members can gain added value if they want to participate in the cooperative. The more often members participate, the greater the added value they get. So that cooperatives can provide added value to members, the cooperative’s performance must be good. One effort that can make cooperative performance better is carrying out internal marketing. Smart marketer realize that marketing activities within the company are usually as important or even more important than marketing activities directed outside the company. It makes no sense to promise excellent service before the company’s staff is ready to deliver it. For this reason, in internal marketing, companies treat their employees as internal customers. The company guarantees the welfare of its employees, because the success of internal marketing depends on the experience of internal customers within the organization. If internal marketing is able to build professional employees who provide excellent service, it will make customers happy. Likewise in cooperatives, if employees can provide excellent service to their members, the members will be happy and participate actively in the cooperative. The better the cooperative’s performance, the greater the cooperative’s ability to improve the welfare of its members. The greater the role of the cooperative in improving the welfare of its members, the higher the member participation in cooperative activities. So, the relationship between cooperative performance, member participation, and member welfare is a mutually influencing relationship. The implementation of internal marketing in cooperatives is not only aimed at employees, but also at cooperative members.